Transformation of the energy sector and its impact on the European Union’s external trade in energy raw materials in 2000–2020 - Mucha-Leszko, Bogumiła; Wojtas, Monika (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The purpose of the paper is to investigate the multifaceted impact of the transformation of the energy sector on domestic economies and international economic relations under the conditions of growing global interdependence. The authors formulate the following research question: What were the changes in the consumption and structure of generating energy, as well as the structure of exports and imports of energy sources, resulting from the transformation of the energy sector in the EU? The following methods were used. The theoretical analysis of the energy sector transformation is based on an interdisciplinary approach proposed by representatives of the International Political Economy. The empirical analysis uses the following indicators: growth rates of energy consumption, shares of selected countries and the EU in the global energy consumption, shares of major sources in the consumption of energy in selected economies, shares of major energy sources in exports and imports of the EU and its member states. Considering the achievements of the EU’s energy policy focused on decreasing the consumption of energy and departing from traditional sources (especially coal) to renewables, the authors concentrate on the results and consequences of the energy policy in the EU. It revealed that the EU had better results on the global scale in limiting energy consumption in 2000–2020. However, the transformation of the energy sector that leads to greater use of renewables is still in the initial stages. Oil and natural gas remain the main sources of energy consumption. When evaluating the impact of transformation on EU energy trade, the dependence on high energy imports in the EU is notable, which actually increased in 2000–2019 from 56.3% to 60.7%. The structure of the imports remained basically the same. The share of oil and natural gas increased slightly, from 88.7% to 89.8%, and the share of renewables climbed from 0.1% to 1.4%. An unfavourable change from the point of view of EU energy policy is the growing share of solid fossil fuels, which was, for the most part, caused by imports to Poland, Slovakia, Czechia and Germany. The structure of exports was quite stable, with oil and natural gas as dominant sources (73.5% and 13.3%, respectively). However, the share of solid fossil fuels in EU exports decreased from 8.8% to 2.8% (2000–2019), which is a positive trend.

Celem pracy jest przedstawienie wieloaspektowego wpływu transformacji sektora energetycznego na gospodarki krajowe i międzynarodowe stosunki gospodarcze w warunkach rosnącej współzależności globalnej. Autorki sformułowały następujące pytanie badawcze: Jakie zmiany transformacja sektora energetycznego UE spowodowała w konsumpcji i strukturze źródeł pozyskiwania energii oraz w strukturze importu i eksportu surowców energetycznych? W pracy zostały wykorzystane następujące metody badawcze. W analizie teoretycznej problemu transformacji sektora energii zostało zastosowane podejście interdyscyplinarne oparte na metodach stosowanych w międzynarodowej ekonomii politycznej. W analizie empirycznej wykorzystano wskaźniki wzrostu konsumpcji energii, wskaźniki udziału krajów i UE w globalnej konsumpcji energii, wskaźniki udziału źródeł energii w konsumpcji energii w wybranych krajach i UE, wskaźniki udziału głównych surowców energetycznych w imporcie i eksporcie UE i jej krajów. Ze względu na osiągnięcia Unii Europejskiej w polityce energetycznej zorientowanej na obniżanie konsumpcji energii i odchodzenie od tradycyjnych źródeł energii (zwłaszcza węgla) na rzecz źródeł odnawialnych, autorki skoncentrowały analizę na wynikach polityki energetycznej i jej następstwach w UE. Wynika z niej, że UE osiągnęła najlepsze rezultaty w skali globalnej w latach 2000–2020 w obniżaniu konsumpcji energii, natomiast transformacja sektora energii w kierunku wzrostu udziału surowców odnawialnych jest w początkowym stadium. Nadal głównymi źródłami konsumpcji energii pozostają ropa naftowa i gaz ziemny. W ocenie wpływu transformacji sektora energetycznego na handel UE podkreślono wysoką zależność krajów UE od importu surowców energetycznych i w latach 2000–2019 ona wzrosła z 56,3% do 60,7%. Struktura importu surowców energetycznych w UE w zasadzie nie zmieniła się. Udział ropy naftowej i gazu ziemnego wzrósł z 88,7% do 89,8%, a udział odnawialnych źródeł energii wzrósł z 0,1% do 1,4%. Zmiana niekorzystna z punktu widzenia polityki energetycznej UE to wzrost importu stałych paliw kopalnych, na co istotny wpływ miał wzrost importu Polski, Słowacji, Czech i Niemiec. Nie zmieniła się też istotnie struktura eksportu UE – dominuje ropa naftowa i gaz (73,5% i 13,3%). Pozytywną zmianę stanowi spadek udziału w eksporcie stałych paliw kopalnych z 8,8% do 2,8% (2000–2019).
Keywords: energy consumption; diversification of energy sources; changes in EU exports and imports; konsumpcja energii; dywersyfikacja źródeł energii; zmiany w eksporcie i imporcie UE